Formulation Of Instant Moringa Oleifera Combination Dates (Phoenix Dactylifera L.) As Galactogogues - Aris Prastyoningsih; Joko Santoso; Erinda Nur Pratiwi; Dheny Rohmatika; Ajeng Maharani; Dewi Andang Prastika (Interest : Jurnal Ilmu Kesehatan, 2022)
Background: Moringa oleivera is a local plant species that has the potential to be developed for nursing mothers. The content of phytosterol compounds contained in Moringa leaves has a function to increase and facilitate the production of breast milk. Instant Moringa powder preparation is one of the processed Moringa powder leaves in the form of powder for drinks that can be used by nursing mothers. Dates contain sterols needed to produce hormones for breastfeeding mothers, such as estrogen, progesterone, and prolactin. This hormone has a very important role in increasing milk production. Methods: Extraction of Moringa leaf powder (15%) and dates (25%) by infundation method with aquadest solvent. Moringa powder extract and date extract were further crystallized with sucrose (60%). Results: The results of the formulation of 30 grams of moringa plus 50 grams of crystallization with 120 grams of sugar obtained as much as 115 grams of moringa powder. The color of the preparation is brownish yellow, the smell is typical of Moringa with a slightly bitter sweet taste, pH is 5.61%, water content is 5.41% and fat content is 1.75%. Conclution: There is a shrinkage during the formulation processing process of 57% of the net weight of the material.